Effects of a magnetic field on circulation in an advanced inclined isothermal sectional surface with mass and heat transfer - SUNDAR RAJ MARIADOSS; NAGARAJAN GNANAVEL; RAJARAMAN R; SARAVANAN B; Muthucumaraswamy R (International Journal of Applied Mechanics and Engineering)
The purpose of this study is to investigate the influence of an external magnetic field on heat and mass distribution across a moving isothermal sectional surface. The temperature is elevated to ( ) of the plate. The proximity intensity is increased to the concentration of the plate ( ). The study addresses a range of physical factors, including time, velocity profile, temperature, and intensity, as well as thermal Grashof number (Tg), mass Grashof number (Tm), Schmidt number (Sc), and Prandtl number (Pr). The dimensionless equations are addressed using both the Laplace-transform technique and the finite difference method, which is used to analyze the energy, momentum, and concentration equations. The results are illustrated through graphical representations, and the tabular manner to showcase various flow parameters. The results indicate that the velocity increases proportionally with changes in (Tg) and (Tm). As the angle (α) rises, the velocity shows a clear incremental pattern when the magnetic field strength decreases. Local skin friction correlates positively with the angle (α), Sc, and Pr, and negatively with Gr, Gc, and time. The study includes a Nusselt number table for various parameters corresponding to an increase in the Prandtl number, as well as the Sherwood number for different components as the Schmidt number escalates. This work helps us learn more about the complicated interactions between magnetic fields and fluid movement, which is useful for many engineering and science projects.